Social Welfare Analysis of Policy-based Finance with Support for Corporate Loan Interest - Changwoo Nam (KDI Journal of Economic Policy, 2021)
We analyze the social welfare effect when a policy-based financial system (PFS) enters a decentralized financial market. Particularly, the PFS in this case supports the interest spread for corporate loans held by firms with heterogeneous bankruptcy decisions under an imperfect information structure. Although support for capital costs through the PFS expands the economy consistently, the optimal level of PFS out of the corporate loan market is estimated to be 8.6% by a simulation model considering social welfare adjusted by the disutility of labor. This result is much lower than the recent level of PFS in the Korean financial sector.
Keywords: E22; G32; G33; 330; Social Welfare; Policy-based Finance; Default Decision; Firm Dynamics